PCPP-260, a Purkinje cell-specific cyclic AMP-regulated membrane phosphoprotein of Mr 260,000 - Walaas, SI (J Neurosci, 1986)
The present study reports the existence of Purkinje cell-specific phosphoprotein, Mr 260,000 (PCPP-260), a neuronal membrane phosphoprotein, in cerebellar Purkinje cells. PCPP-260, which on sodium dodecyl sulfate-polyacrylamide gel electrophoresis has an apparent molecular mass of 260,000 Da, has been found to be phosphorylated in particulate preparations by endogenous or added exogenous cyclic AMP- dependent protein kinase, but not by cyclic GMP-dependent, calcium/calmodulin-dependent or calcium/phospholipid-dependent protein kinases. The protein has been found in high concentrations in all mammalian cerebella so far analyzed, including human cerebellum. One- and two-dimensional electrophoretic and peptide mapping analyses of proteins in other brain regions show that a closely related 265,000 Da phosphoprotein also exists, albeit in low concentrations, outside the cerebellum. Analysis of cerebella from mutant mice, deficient in either Purkinje cells or in granule cells, indicates that PCPP-260 within the cerebellum is restricted to Purkinje cells. Furthermore, subcellular fractionation of rat cerebella indicates that the protein is an integral membrane protein. The cAMP-regulated phosphorylation of PCPP- 260 is presumably involved in membrane functions important to Purkinje cells.